Structural relationship model of factors affecting the organizational performance of UAE oil & gas industry - Taher Al Mansoori, Fatima (2021)
There are many issues and challenges faced by oil & gas industry performance such as shifting technology, skill workforce, retains experienced expertise and others. Thus, it drives this study to establish a structural equation model of factors affecting the UAE oil & gas industry performance. These factors were clustered into five independent variables which are Leadership, Training, Motivation, Organizational culture, Job satisfaction. This study adopted quantitative approach. It used questionnaire to collect data where the questionnaire was validated by 18 experts from UAE oil & gas industry. For data collection, it adopted non-probability sampling of simple random technique of survey among oil & gas practitioners. Even though the survey has low response rate of 26.25% but still within the minimum requirement sample size for model development. The collected data was analysed descriptively and found five most significant factors affecting the oil & gas organizational performance are rewards and recognition, low employee turnover, effective behaviour, assuring job security and effective support system. Then the collected data was used to developed and assessed PLS-SEM model of casual relationship of factors affecting oil & gas organizational performance using SmartPLS software. The model was assessed at measurement and also structural levels and found that it has achieved all the fitness criteria. It was found that the developed model has substantial validating power of 43.6% which representing the impact of the five groups of factors on the organizational performance. For hypothesis testing, only two out of five hypotheses are having significant relationship which is leadership and job satisfaction groups. Since, literature indicated that is no such model, then the establishment of this model is the main contribution to the body of knowledge. It also can assist the relevant stakeholder of the oil & gas organization in improving their performance.